1996
DOI: 10.1001/archpsyc.1996.01830070031007
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Human Brain Morphometry and Metabolism: An In Vivo Quantitative Magnetic Resonance Imaging and Positron Emission Tomography Study on the Effect of Aging

Abstract: We found significant sex differences in aging of brain areas that are essential to higher cognitive functioning. Thus, our findings may explain some of the age-sex differences in human cognition and response to brain injury and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
271
4
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(312 citation statements)
references
References 83 publications
34
271
4
2
Order By: Relevance
“…The finding of accelerated loss in hippocampus is somewhat surprising, given the inconsistency of previous results regarding the degree of age-related loss present in this structure. Sullivan et al [39] reported no age-related loss in hippocampus, while highly significant losses were reported by Murphy et al [31]; and clinical ratings of peri-hippocampal fluid increases also suggested age-related hippocampal atrophy [13]. Although the sample sizes were similar for these studies, the age-range examined was extended in the latter two studies, as it was in the present study, relative to the former.…”
Section: Regional Variability In Gray Matter Losssupporting
confidence: 47%
See 2 more Smart Citations
“…The finding of accelerated loss in hippocampus is somewhat surprising, given the inconsistency of previous results regarding the degree of age-related loss present in this structure. Sullivan et al [39] reported no age-related loss in hippocampus, while highly significant losses were reported by Murphy et al [31]; and clinical ratings of peri-hippocampal fluid increases also suggested age-related hippocampal atrophy [13]. Although the sample sizes were similar for these studies, the age-range examined was extended in the latter two studies, as it was in the present study, relative to the former.…”
Section: Regional Variability In Gray Matter Losssupporting
confidence: 47%
“…These have confirmed volume decreases in cortical gray matter [2,31,33,34,39], cerebral hemispheres [7,8], and basal ganglia structures [27,30,35], and increases in volumes of [15,28], or odds of [8], signal hyperintensities in the white matter. In some studies, such as our previous study, white matter volume did not appear to change with age [2,19,33].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, when examining the sample split by gender, the negative association only remained for the women. Although the propensity of the literature supports similar age‐related hippocampal volume loss for men and women (Jack et al., 2015; Mu, Xie, Wen, Weng, & Shuyun, 1999; Raz et al., 2004, 2005), there are reports of both women‐ and men‐specific age–hippocampal volume relationships (Murphy et al.,1996; Pruessner et al., 2001). For the current sample, the lack of significant association in the men may be explained by this gender not experiencing a similar age‐related trajectory in hippocampal volume, and therefore not experiencing the benefits of CRF on hippocampal volume.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, this interaction was not expected because most longitudinal studies report either no differences in the age-related decline in cognitive functions for men and women (Aartsen et al, 2004), or, when gender differences are observed, a more pronounced decline for females (Meinz & Salthouse, 1998). However, volumetric imaging studies have shown a stronger effect of aging on the frontal lobes in men than in women (Cowell et al, 1994;Murphy et al, 1996). This finding may explain the age 3 gender interaction found for the SCWT Interference change score.…”
Section: Assessment Of Change 77mentioning
confidence: 99%